Exploring readiness to adopt AI: Junior executives’ perspective - Armanshah, Nurshazana Aiman (2023)
Malaysia is ranked as one of the most famous countries in Southeast Asia that have advanced technology. So, it is not surprising if Malaysia starts to embrace artificial intelligence into the country as AI is well-known as a technology that revolutionized the way how people live and work. The main aim of this study is to explore readiness to adopt AI among organizations in Malaysia. Hence, a qualitative approach was conducted. In this qualitative study, 10 participants were interviewed to get their opinions regarding their knowledge on AI, their perception towards AI, explore level of AI adoption in their organization and their advice to organization that plan to adopt AI. From the interview, the study found that Malaysian organizations are aware about AI but surprisingly, not all is adopting AI in their organization. In fact, majority of the participants do agree that AI is a good technology that should be adopted. Among the reasons shared for not adopting AI in the organization are financial issue, lack of expertise, lack of knowledge and AI is not needed at the moment. The participants also shared their advice to conduct readiness audit before embarking on AI. The audit will allow the organization to examine the size and capabilities of the organization to adopt AI. This current study makes a vital contribution to understand and acknowledge the readiness of Malaysian organizations in adopting AI. The implication and future research direction are outlined to allow others to explore the other scopes of study.